FITUR PEMBUATAN BAHAN AJAR BERUPA HANDOUT DENGAN FRAMEWORK LARAVEL PADA SISTEM INFORMASI PEMBERKASAN PERKULIAHAN BERBASIS WEB - Febi Eka Febriansyah; Akmal Junaidi; Rangga Firdaus; Rendi Eko Prasatiawan (Jurnal Pepadun, 2021)
Lampung University is one of the state universities in Lampung Province with a variety of faculties and departments. One of which is the Faculty of Mathematics and Natural Sciences that includes the Department of Computer Science. The Department of Computer Science applies the process of compiling lecture devices into a system. The preparation of lecture equipment cannot be separated from the tools or equipment of teaching materials because they are needed in the learning process of each subject. At this time the process of compiling teaching materials on the web-based lecture filing information system in the Department of Computer Science has not been applied using the system. Therefore, with the addition of the feature of making teaching materials in the form of handouts with the Laravel framework on a web-based lecture filing information system, it is hoped that it can assist lecturers in preparing teaching materials and assist administrators, faculty, and students in finding teaching materials so that they can be printed. The conclusion of this research is that the feature of making teaching materials in the form of handouts with the Laravel framework on a web-based lecture filing information system has been successfully added.